Moneyball and soccer - an analysis of the key performance indicators of elite male soccer players by position - Hughes, M.; Caudrelie, T.; James, N.; Donnelly, I.; Kirkbride, A.; Duschesne, C. (Journal of Human Sport & Exercise, 2012)
In most sports, it is found that the important performance indicators (PI`s) vary from coach to coach. Therefore, if sets of PI`s can be identified and clear operational definitions defined, there is significant scope/benefit for consultancy and research, particularly in commercially orientated sports such as soccer. The aim of this study was to use the unique opportunity of a large number of performance analysts coming together to discuss this problem and its application to soccer, and define sets of performance indicators for each position in soccer. In the early spring of 2011, staff from 9 universities, from all over Europe, brought 51 level 3 Sports Science students to Hungary for an Intensive Programme in Performance Analysis of Sport (IPPAS). The 15 staff, all experts in PA, had a total of over 200 years of experience of PA between them. The most experienced `experts` (N=5) acted as mentors, introducing the area, defining the aims and managing the groups. The rest (N=10) and the 51 students were distributed evenly as possible across 7 groups, in which their aim was to define the key PI`s for one of the positions in soccer. The positions used were:- Goalkeepers; Full Backs; Centre Backs; Holding Midfield; Attacking Midfield; Wide Midfield and Strikers. In conclusion, 7 sets of KPI`S, were defined for each of these classifications within 5 category sets: Physiological, Tactical, Technical - Defending,Technical - Attacking, and Psychological. These KPI`s were different from position to position within the team, particularly for the Goal Keeper. The KPI`s for the outfield players were very similar, differing only in their order of importance. This enabled a `generic` set of skills required for outfield players in soccer.